Tinjauan Yuridis Terhadap Pelanggaran Lalu Lintas Akibat penggunaan Smartphone Yang dapat Menghilangkan Konsentrasi Saat Berkendara - Salampe, Andi Akbar Ramdhan; Erlina; Hamsir; Basri, Ade Darmawan; Safriani, Andi (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2025)
The aim of this research is to identify the elements of criminal acts and sanction threats associated with using smartphones while driving, as well as the underlying reasons. This study uses a case approach, which is a normative legal research method that builds legal arguments based on concrete cases. The research is a bibliographic study with a normative juridical qualitative method that refers to legal norms in statutory regulations. Using smartphones while driving violates Law No. 22 of 2009 concerning Road Traffic and Transportation, with a maximum fine of Rp. 750,000.00, which may be reduced in court. The main reasons are urgent calls from family or work and the need for GPS navigation. It is expected that the government will establish clearer guidelines for using GPS on smartphones to ensure driver safety and support jobs like online motorcycle taxis. Law enforcers should educate drivers about the penalties for violations.